Isolation of RNA aptamers specific toward 16 KDA mycobacterium tuberculosis antigen protein - Mohammed, Nurul Adila (2020)
Tuberculosis (TB) is an old, infectious disease scourge caused by Mycobacterium tuberculosis (M.tb) that affects human. There are several laboratories diagnostic methods available for TB screening such as sputum smear microscopy, culture and nucleic acid amplification that can diagnose patients with active TB. However, the methods are not for detection of latent TB infection (LTBI). Despite the advent of Interferon Gamma Release Assay (IGRAs) for diagnosis of LTBI, the test is expensive and laborious. The test is also not accessible for poor countries that have high TB burden due to cost and lack of rapid point-of-care setting. Thus, a new point-of-care technology is urgently needed to improve the current LTBI diagnosis to more economical and easily implemented technology especially for low resource settings countries. So far, aptamers have received considerable attention due to its properties that could imitate function of antibody against the target with high specificity and affinity. The 16 kDa protein of M.tb. was selected as a prime candidate for this study due to its importance in immunodominant property and tuberculosis latency. Thus, this study was aimed to isolate and characterise the RNA aptamers against the 16 kDa protein. By performing Systematic Evolution of Ligands by Exponential Enrichment (SELEX) method using nitrocellulose membrane, the RNA aptamers against 16 kDa protein were successfully isolated and characterised. The isolated aptamers were then clustered together based on their nucleotide homology sequences, while the secondary structure, motif sequence and Gquadruplex analysis were identified using free online software. Electrophoretic Mobility Shift Assay (EMSA) was performed using agarose gel electrophoresis to determine the binding and the dissociation constant (Kd) value for each isolated RNA aptamer. Out of five isolated clusters of RNA aptamers, the cluster (TB_APG01) was had the nucleotide sequences with the highest frequency clones (14/104) and Kd value 6.428±4.97 μM, however the cluster TB_APG04 was recognized as the strongest aptamer with the lowest Kd value (3.935±1.60μM) although only have 2/104 clones. As a conclusion, this study was successfully isolated the RNA aptamers that bound to the 16 kDa protein and maybe useful for direct LTBI diagnosis or as imaging tool.